The developing child - Bee, Helen L., 1939-; Boyd, Denise Roberts (Boston : Allyn & Bacon, 2010)
Product Description: The Developing Child gives students the tools they require to organize, retain and apply information from the broad field of child psychology, while offering balanced coverage of theory and application, with a strong emphasis on culture. Key Topics: Prenatal Development; Birth and Early Infancy; Physical Development; Perceptual Development; Cognitive Development; Development of Language; Personality Development; Development of Social Relationships; Family System; Atypical Development. For individuals seeking to understand to better understand children. Want to learn more about MyVirtualChild? Visit www.mydevelopmentlab.com and click on the'watch this video' link to learn about MyVirtualChild. MyDevelpmentLab with MyVirtualChild is available at www.mydevelopmentlab.com.
Includes bibliographical references (p. 459-519) and index.
Keywords: Child psychology -- Textbooks; Child development -- Textbooks